Maternal and perinatal impact of gender-based violence - Távara Orozco, Luis (2015)
Objective: To recail abuse prevalence against women attended at Lima's South Cone obstetrical services and to establish association between violence and both maternal and perinatal pathology and perinatal mortality. Design: Analytical retrospective cohort investigation. Setting: Maria Auxiliadora Hospital and Cesar Lopez Silva Mother and Child Hospital, Villa El Salvador. Participants: Hospitalized puerperal women. Interventions: Between March and november 2005 we applied a survey to 7333 puerperal women before discharge from the hospital in order to identify the presence of violence against women. Answers were classified in three groups: without violence (30,7%), with violence history (37,4%) and with violence during this pregnancy (31,9%). Wereviewed the perinatal clinical history in each case and verified demographic variables as well as maternal and perinatal complications. We also determined both fetal or neonatal deaths. Data was processed in Epi Info V.6. in order or examine differences, we applied X2 and student t and we considered statistically significant when p<0,05. Main outcome measures: Violence during pregnancy, obstetrical and neonatal complications. Results: In the violence during pregnancy group the higher frequency of obstetrical and neonatal complications was significant, as well as higher perinatal mortality. Conclusions: Gender based violence is very frequent in the pregnant population attended at lima's South Cone and is associated with higher maternal and perinatal pathology frequency and higher perinatal mortality.